The Influence of Macroeconomics Factors and Political Risk on the Sukuk Market Development in Selected GCC Countries: A Panel Data Analysis - Zainol, Zairy; Abdul Rahim, Ahmad Khilmy (Universiti Kebangsaan Malaysia, 2019)
In light of the countries’ attempt to develop their economies and follow stable macroeconomic policies that stimulate the sukuk markets and the stress placed on the political stability of the countries, investigating the role of political risk and macroeconomic factors is crucial to sustain a country’s Islamic financial development. Therefore, this study used the panel data to examine the influence of the macroeconomic factors and political risk on the sukuk market development in the selected GCC countries, namely Saudi Arabia, United Arab Emirate, Bahrain, Qatar and Kuwait from 2001 to 2016. The model of sukuk market development is extended by incorporating the six specific characteristics of GCC countries. The diagnostic tests affirm that the most preferred model to explain the determinants of sukuk market development is by using the Pooled Ordinary Least Square (POLS) Model. The findings reveal that the banking sector and exchange rates are negative and have significant effects on the sukuk market development. The consideration of the increasing level of trade openness is vital due to its major contribution to enhance the sukuk market development. Interestingly, this study finds a positive significant association between the political risk and the sukuk market development. In order to promote the sukuk market development in the region, it is important to develop strategies for integrating and linking the banking sector and the sukuk market in order to promote the sukuk market by creating a scale economy and the required financial market infrastructure